Global food value chains and competition law / edited by Ioannis Lianos, Alexey Ivanov, Dennis Davis. - Lianos, Ioannis; Ivanov, Alekseĭ I͡Urʹevich; Davis, Dennis (Global competition law and economics policy., 2022)
The food industry is a notoriously complex economic sector that has not received the attention it deserves within legal scholarship. Production and distribution of food is complex because of its polycentric character (as it operates at the intersection of different public policies) and its dynamic evolution and transformation in the last few decades (from technological and governance perspectives). This volume introduces the global value chain approach as a useful way to analyse competition law and applies it to the operations of food chains and the challenges of their regulation. Together, the chapters not only provide a comprehensive mapping of a vast comparative field, but also shed light on the intricacies of the various policies and legal fields in operation. The book offers a conceptual and theoretical framework for competition authorities, companies and academics, and fills a massive gap in the competition policy literature dealing with global value chains and food.